Franchising decision support system for formulating a center positioning strategy. Issue 5 (8th June 2015) - Wu, C.H.; Ho, G.T.S.; Lam, Cathy H. Y.; Ip, W.H.
Abstract : Purpose: – The purpose of this paper is to propose a franchising decision support system (FDSS) for future development planning by center positioning strategy formulation under a franchising business model. Design/methodology/approach: – The system makes use of data collected from the franchising business and external environment analysis for decision making in center positioning problems. The fuzzy logic approach is integrated into the system for analyzing the geographical market dynamics including profitability and competitiveness in the district concerned. To demonstrate the application of the proposed FDSS, a case study is conducted in a Hong Kong-based franchising private education center, i.e. Dr I-Kids Education Center. Findings: – The tailor made FDSS helps to facilitate the business operations of the franchising education center and develops a district positioning model for the centers located in the 18 districts of Hong Kong. The findings provide a solid foundation for marketing strategy and expansion direction formulation. Originality/value: – Due to the globalization of business, managing a growing franchising business model becomes challenging to the franchisor. In order to fully leverage the merits of the franchising system, an intelligent decision support model, focusing on making strategic development plans, is needed so as to expand the scale of business efficiently.